Assessing and improving the knowledge of sexually transmitted infections among freshers in the selected universities, Magway - Aye, Khin Cho; Htwe, Yin Yin; Aung, May Oo; Aung, Htet Phyo (International Journal Of Community Medicine And Public Health, 2025)
Background: To alleviate the public burden of sexually transmitted infections (STIs), one of the effective strategies is to improve the knowledge and awareness of STIs, especially among high-risk populations. This study aimed to assess the baseline knowledge score on STIs among freshers and to evaluate the effectiveness of a health education program on STIs. Methods: A cross-sectional comparative study, incorporating pre-test and post-test design with a health education program, was conducted using a self-administered questionnaire among 110 freshers from medical-related university and 110 from non-medical university in Magway in 2023. Data analysis was done by R. Results: Regarding the types of STIs, almost all (217, 97.7%) of the freshers identified AIDS as STI followed by syphilis (131, 59.5%) and gonorrhea (83, 37.7%). Concerning the modes of transmission, nearly all (216, 98.2%) identified sexual contact. About 39 (17%) of the freshers stated that they did not know the signs of STIs whereas 11, 5% were unaware of the complications. For the prevention of STIs, many students (208, 94.5%) stated the use of condoms. A statistically significant difference in baseline STIs knowledge scores was observed between the medical-related (25.1±5.9) and non-medical university (21.2±5.7) students (p<0.001), as well as between males (24.2±6.0) and females (21.5±5.7) (p<0.001). Following the health education session, there was a significant mean improvement of 14.4 points in post-test score (p<0.001). Conclusions: This data highlighted the need for health education programs on STIs among university students.